Analysis of the Influence of Leading Sectors on Economic Growth in Lombok Timur Regency 2012-2022 - Muh Khairul Fatihin; Muaidy Yasin; Emi Salmah (Tinta Emas Institute, 2023)
Economic growth is an indication of the success of economic development in people's lives. Economic growth shows the growth in production of goods and services in an economic area within a certain time interval. This research aims to analyze the determination of leading sectors and their influence on the economic growth of East Lombok Regency in 2012 - 2022. A descriptive approach with a quantitative approach. Data collection techniques involve literature study and documentation, with data obtained from the Central Statistics Agency (BPS) of East Lombok Regency and West Nusa Tenggara Province. The analysis used is multiple linear regression. The results of this research are the Wholesale and Retail Trade sectors; Car and Motorbike Repair has a significant positive influence with the second largest contribution to GRDP, reaching around 17.46 percent in 2022. In contrast, the Real Estate sector does not show a significant influence on economic growth, with a stagnant contribution of around 3.63 percent. Meanwhile, the Government Administration sector; Defense and Mandatory Social Security did not have a significant effect, although their contribution stagnated between 6.83 percent and 7.44 percent. This conclusion reflects the dynamics of these sectors in supporting or limiting economic growth in East Lombok Regency, in line with findings in previous research.